Primary physical education subject leadership: along the road from in-house solutions to outsourcing. Issue 6 (18th August 2019) - Griggs, Gerald; Randall, Vicky
ABSTRACT: The modern primary school is a complex institution containing a growing community of individuals and organisations with potentially competing agendas. Within this environment, subject leaders are typically looked upon for advice and guidance within a given subject area such as Physical Education. Yet for those endeavouring to provide Physical Education subject leadership within primary schools, the challenge has grown significantly over the last two decades amidst an ever-changing policy landscape. This paper is for and about primary Physical Education subject leadership; the purpose of which, to plot primary Physical Education's policy journey and explore the implications of reform in shaping the subject leader's role. The paper addresses the current lack of guidance for the subject leader and examines the professional knowledge, skills and experience required to do the role effectively.